Do Surrogate Markers for Adiposity Relate to Cytokines in Adolescents?. (1st June 2008) - Rubin, Daniela A.; McMurray, Robert G.; Harrell, Joanne S.; Hackney, Anthony C.; Haqq, Andrea M.
Abstract : Purpose: To determine the associations between field-collected surrogates of adiposity and concentrations of resistin, tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and adiponectin in youth. Methods: Cross-sectional data from 60 normal weight and 60 overweight adolescents, ages 10-14 years, were retrospectively examined. Body mass index (BMI) percentile, sum of subscapular and triceps skinfolds (SSF), and waist circumference (WC) were used to classify weight status (BMI) or adiposity (SSF and WC). Percentiles for each surrogate were used for comparison groups. Fasting TNF-α, IL-6, resistin, and adiponectin concentrations were measured in plasma. Results: Multiple regression models, controlling for sex and ethnicity, indicated that TNF-α was associated with BMI percentile ( R 2 = 0.107, P < 0.05) and SSF ( R 2 = 0.085, P < 0.05), whereas resistin was associated with SSF ( R 2 = 0.118, P < 0.05). Adiponectin was associated with all 3 adiposity markers: BMI percentile ( R 2 = 0.298, P < 0.05), SSF ( R 2 = 0.297, P < 0.05), and waist ( R 2 = 0.278, P < 0.05). Analyses of variance indicated higher TNF-α and lower adiponectin concentrations in youth with a BMI higher than the 95th percentile ( P = 0.014; P < 0.001) or SSF higher than the 95th percentile ( P = 0.025; P < 0.001). Youth with WC higher than the 90th percentile had higher resistin ( P = 0.029), higher IL-6 ( P = 0.028), and lower adiponectin ( P < 0.001) concentrations. Conclusions: Of the 3 surrogates examined, differences in cytokine concentrations were mostly observed in youth who had WC percentiles higher than the 90th percentiles versus WC lower than the 75th percentiles. Alternatively, from the multiple-regression models SSF, an estimate of subcutaneous adiposity was the surrogate most consistently related to all cytokines, although the degrees of associations were low. The results suggest that although some surrogates were more strongly associated to certain cytokines, WC and SSF seemed more closely associated with cytokines than a BMI percentile indicating obesity.